(3HQfGeL Mbhb GdWad(B: (3JbQjQ Yf hQTI Yed EbdjejI Mhd Mbhb GdWad hGdGbJUGO Gdcdjs - (3MLGQ, jhSas ((3HjQhJs (3hQTI GdehGQO GdYQHjIs, 2000)
(3jhKb GdJbQjQ CYeGd hQTI GdYed GdEbdjejI GdJj JfOQL aj eTQhYGJ HGOQJ efXeI QYGjI GdCWaGd GdShjOjI Edi EWdGbg efP eWdY GdYGe (B1998(3, jHfi Ydi GdQHW Hjf GdGbJUGO Gdcdj hHjf Mbhb GdWad aj GdeLJeYGJ GdeNJdaI(B. (3gOaJ hQTI GdYed Edi GSJcTGa GdYdGbI Hjf GdGbJUGO Gdcdj hMbhb GdWad (B((3CTcGdgG hJCKjQgG aj aQU GYeGd cd Mbhb GdWad, GdJYQa Edi MGLGJ GdYGedjf aj GdefGOGI HMbhb GdWad, JYQja GdGbJUGOjjf hGdeTQYjf HMGLGJ GdCWaGd hhGbYge hMbhbge hJWhjQ (B"(3TQGcGJ Yed(B" (3JVY gPg GdMGLGJ hGdMbhb Ydi NGQWI GdChdhjGJ GdGbJUGOjI hGdEfaGb GdeGdj, GSJcTGa GdHMhK hGdeHGOQGJ PGJ GdUdI aj GdHdOGf GdYQHjI hHMK SHd GdGSJaGOI efgG hJWhjQgG hfTQgG(B.s
(3GdfhY (B: (3cJGHs
Keywords: Children Rights; Droit de L$1 (Benfants; Les Facteurs Socio- Economiques; Social and Economic Factors; (3GdYhGed GdGLJeGYjI hGdGbJUGOjIs; (3Mbhb GdWads; (3Mbhb GdWads